¿Por fin menores civilmente responsables? Reflexiones a proposito de las reformas de 2015 - M. Yzquierdo Tolsada, Mariano (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2017)
The Spanish legal system regarding injuries caused by minors and legally incapacitated is the most complex in the world, but there are some recent legal news which clearly allow that —way beyond the rules penned in the Civil Code— those offenders who committed the injuries are also responsible for the latter and not just the parents or the keepers.
Keywords: Minors; extra-contractual liability; Civil Law; 2015 reforms; imputability.